A four‐fold regional‐specific approach to TQM: the case of South Eastern Europe - Alexandros Psychogios (2010)
Purpose: This paper aims to increase understanding of the application of total quality management (TQM) initiatives in business environments that differ from those where it emerged. Organisations within such environments, which are often less developed, may wish to adopt relatively sophisticated initiatives such as TQM. The adoption of TQM programmes by a variety of private and public sector organisations in South Eastern Europe (SEE) is a prime example. Little has been said about the awareness and applicability of TQM in this region. Design/methodology/approach: A combination of quantitative and qualitative research approaches was used. The quantitative results emerged from the investigation of 782 managers working in 123 service organisations in public and private sectors (51 and 72 respectively) in four major SEE countries, namely Romania, Serbia, Bulgaria, and Greece. Subsequently, for triangulation and to provide richer data, 34 follow‐up semi‐structured interviews were conducted with managers from these four countries. Findings: After having carried out quantitative and qualitative analyses, a four‐fold model emerged, through which key features of the application of TQM practices in the SEE region could be explained. The components of the model are categorised in two major groups; first, the influences of the business/management culture and modernisation pressures, and second, two key aspects of the business systems – the education level of managers and the sector of employment. Research limitations/implications: Both cultural and structural features of the business systems in SEE create pressures either promoting or retarding TQM adoption within organisations. The paper provides a four‐fold factors model that aims to explain key regional‐specific issues related to TQM adoption. This approach provides insights into the region studied, but also provides a prototype for similar studies in other regions. Practical implications: In the SEE context, the tension between traditional business/management culture and modernisation logic is the key to the evolution of TQM. SEE managers adopt a more pragmatic view of TQM application through the use of “hard” quality management systems and practices, while placing less importance on concepts such as empowerment and employee involvement. Originality/value: The study argues for the adoption of a regional‐specific view of TQM, applicable to particular regional business systems.